Ligand-Free BaF2: Nd Nanoparticles With Low Cytotoxicity, High Stability and Enhanced Fluorescence Intensity as NIR-II Imaging Probes - Cui, Xiaoxia; Xu, Yantao; She, Shengfei; Xiao, Xusheng; Hou, Chaoqi; Guo, Haitao (Frontiers in Physics, 2021)
Ligand free BaF2: Nd nanoparticles with a size of 10 nm were fabricated by a novel synthetic route in the liquid phase. A transparent dispersion of the BaF2: Nd nanoparticles mixed with propanetriol and DMSO-d6 was developed. High stable and outstanding near-infrared (NIR) fluorescence centered at 1058 nm was detected exciting with an 808 nm laser. Moreover, the dispersion can be stable settled over one month and the cytotoxicity of the BaF2: Nd nanoparticle dispersion has also been studied by MTT assay approach. The superior performance of these nanoparticles proclaims the great potential application in the high-contrast and high penetration in-vivo imaging.